Label Style and Color Contribution to Explain Market Price Difference in Italian Red Wines Sold in the Chinese Wine Market. Issue 2 (3rd April 2018) - Galati, Antonino; Tinervia, Salvatore; Tulone, Antonio; Crescimanno, Maria; Rizzo, Giuseppina
ABSTRACT: This study employs a hedonic price methodology to investigate the implicit price of individual labelling characteristics of Italian red wines sold in the Chinese market. Our results highlight the most important quality attributes (extrinsic and intrinsic) given in the label capable to explain price difference. In particular, reveal significant premium price for wine origin, identified in particular through the DOC/DOCG appellation given in the label, and for clean labels or labels with particular designs. On the contrary, a price discount has been revealed for Italian wines produced with local grape varieties and with a label characterised by warm colors. These results, partly in disagreement with other empirical evidence, contribute to enrich the existing literature in this field by providing useful suggestions both to the producers and other stakeholders operating in the wine industry.